IMPLEMENTATION OF SPIRITUAL TRAINING MIRACLE OF HAPPINESS FOR SUKU ANAK DALAM (SAD) IN MUARA TIKU VILLAGE, MUSI RAWAS UTARA DISTRICT - Afriantoni, Afriantoni; Asnita, Roma Nur (LPPM Univ. Ibn Khaldun Bogor, 2024)
The community service activity conducted by Raden Fatah State Islamic University (UIN) in Palembang aims to enhance the quality of education for the youth of the Anak Dalam (SAD) tribe in Muara Tiku Village, Karang Jaya District, Musi Rawas Utara Regency, South Sumatra. In an effort to improve the education of SAD youth, a spiritual approach that integrates local wisdom and local religious teachings is considered an effective solution. This community service program, titled